Pengembangan Startup Digital Mahasiswa Melalui Program Inkubasi Bisnis Digital Pada Universitas Sumatera Utara : Indonesia - Harumy, Henny Febriana; Dewi Sartika Br. Ginting; Fuzy Yustika Manik; Nuzuliati (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2025)
Abstract: Digitalization 5.0 has opened wide opportunities for students to build digital-based startups. However, many student startups face challenges in financial management, developing a Minimum Viable Product (MVP), and ensuring business sustainability. This program aims to implement Digital Business Incubation as a strategy for developing student digital startups. The methods used include observation, tenant selection, interviews, and intensive mentoring for incubation program participants. As a result of the selection process, 14 businesses were chosen to be incubated, consisting of service-based and product-based ventures. The program is designed to provide entrepreneurship training, financial management workshops, business legality assistance, investor networking opportunities, and technological support. The outcomes of the program indicate that through digital incubation, average 77,91% of the participating students were able to enhance their digital entrepreneurship skills, strengthen their business models, and optimize the potential for business sustainability. Therefore, Digital Business Incubation has proven to be an effective mechanism for fostering the growth of student digital startups that are adaptive, innovative, and competitive in the digital economy era. Keywords: bussiness digital, enterprise, student, service Abstrak: Digitalisasi 5.0 telah membuka peluang luas bagi mahasiswa untuk membangun usaha rintisan (startup) berbasis digital. Namun, banyak startup mahasiswa menghadapi tantangan dalam hal pengelolaan keuangan, Minimum Viable Product, dan keberlanjutan usaha. Program ini bertujuan untuk mengimplementasikan program Digital Business Incubation sebagai strategi pengembangan startup digital mahasiswa. Metode yang digunakan meliputi observasi, seleksi tenant, wawancara, serta pendampingan intensif terhadap peserta program inkubasi. Dari hasil seleksi terpilih 14 usaha yang akan diinkubasi yang terdiri dari usaha yang bergerak dibidang jasa dan produk. Program ini dirancang untuk memberikan pembinaan kewirausahaan, pelatihan keuangan, pendampingan legalitas usaha, akses bersama investor, serta dukungan teknologi. Hasil program ini menunjukkan bahwa melalui inkubasi digital, rata rata 77,91% mahasiswa mampu meningkatkan keterampilan wirausaha digital, memperkuat model bisnis, serta mengoptimalkan potensi keberlanjutan usaha. Dengan demikian, Inkubasi bisnis digital terbukti menjadi mekanisme efektif dalam mendorong lahirnya startup digital mahasiswa yang adaptif, inovatif, dan berdaya saing di era ekonomi digital. Kata kunci: bisnis, mahasiswa, jasa, startup digital